Numerical Study on the Effect of Wall Thickness on the Combustion Characteristics of Non-premixed Hydrogen Micro-jet Flame - Li, Xing; Xie, Shengrong; Zhang, Jing; Zhao, Daiqing; Wang, Xiaohan (Frontiers in Energy Research, 2022)
The effect of wall thickness on combustion characteristics of non-premixed hydrogen micro-jet flames were studied by two-dimensional numerical computation with a detailed reaction kinetics for the development of hydrogen burner. The hydrogen jet diffusion flames achieved by micro fuel tubes with the same inner diameter and length but different wall thicknesses were computed. The heat exchange between solid tube and gases were included in the numerical computation. The distributions of flame temperature, OH radicals, details of thermal interaction and combustion efficiency were analyzed for comparison. It was found that the temperature distribution, flame shape and heat recirculation effect are varied with the fuel flow velocity, and they are affected by the wall thickness. The mechanism of wall thickness on the combustion characteristics of hydrogen jet diffusion flame was analyzed. Finally, an interesting numerical experiment was conducted to give a further explanation of the effect of heat recirculation and to provide guidance of thermal management of the micro burner.